Laporan Keuangan Entitas Syariah Sebagai Alat Ukur Kinerja Bisnis - Djaka Suryadi (Jurnal Asy-Syukriyyah, 2014)
The meter has become a standard work agreed Indonesian Accounting Standards SFAS No.101 , 2007, in assessing the financial performance of a business field which is run in a given period , evidenced in the form of accounting reports or financial statements referred to sharia . External factors affecting financial performance include : internal influences such as company politics , legal barriers to enterprise , employment , monopoly , the external environment of the company; regulations of the company , for example : selling price regulation / input prices , taxation , corporate governance , etc. . Needs of Islamic financial statements presented course tailored to its business such as , field services ; field of trade ; fields Manufacture . Furthermore, the parties who require such financial statements have particular concern to the financial statements are presented , namely : Management , Owner , Lender , Investor , Supplier , Buyer , employees , government agencies including the IRS , the Department of Industry , Department of Commerce , and the General Public . The common types of financial reports presented to the parties typically include : statements Balance Sheet, Profit and Loss reports , usage reports and Source of Funds , Cash reports , reports Change Capital , and reports Ratio Analysis , Fund charity and benevolence Fund ( paragraph 8 of SFAS 101 , 2007) to facilitate the readers to read the financial statements are presented , should be attached to the disclosure of each item in the financial statements of the sharia . The financial statements are presented in accordance with GAAP in 2007 is : understandable , relevant , materiality , reliability , honest presentation , substance regale form , neutrality , healthy growth , completeness , can be compared .